Mechanisms of disease: Selective inhibition of 11beta-hydroxysteroid dehydrogenase type 1 as a novel treatment for the metabolic syndrome. - Tomlinson, J; Stewart, P (2005)
The magnitude of the obesity and metabolic syndrome epidemic has heightened the need for the development of new and effective treatments. Although circulating cortisol concentrations are not elevated in obesity or in the metabolic syndrome, decreasing the tissue-specific generation of cortisol through inhibition of 11beta-hydroxysteroid dehydrogenase type 1 (11beta-HSD1) has been postulated as a therapeutic strategy. Observations in cohorts of obese patients, in comparison with those with type 2 diabetes, have suggested that the ability to decrease tissue-specific cortisol production might represent a protective mechanism to improve insulin sensitivity and prevent diabetes. In rodents, pharmacologic exploitation of this mechanism, through the development of inhibitors selective for 11beta-HSD1 (in preference to the type 2 isoform), dramatically improves insulin sensitivity. Here we review the published data and the rationale for treatment in humans, as well as discussing potential problems and adverse effects of future selective 11beta-HSD1 inhibitors.